RESPON TANAMAN SAWI HIJAU (Brassica juncea L. Var. Tosakan) TERHADAP PEMBERIAN PUPUK ORGANIK DAN AZOTOBACTER PADA TANAH MASAM - Agustini, Rika Yayu; Muharam, Muharam; Setiawan, Muhammad Ghozi (Program Studi Agribisnis Fakultas Pertanian, 2024)
Acid soils are characterized by low pH (<5.5) and high Al concentration. Organic fertilizers can provide nutrients, can also increase the pH of the soil, and reduce Al levels in the soil. In addition, the addition of Azotobacter bacteria can increase N nutrients and reduce Aluminum stress in the soil. The purpose of this study was to obtain the types of organic fertilizers and Azotobacter that provide the best results on the growth and yield of green mustard plants (Brassica juncea L.) on soils with high Aluminum content. The research was conducted at UNSIKA New Land, Pasirjengkol Village, Majalaya District, Karawang Regency, West Java Province. The design used was a Factorial Randomized Group Design (RAK) consisting of 6 treatments repeated 4 times to obtain 24 experimental units. The first factor is the type of organic fertilizer (K) which consists of 2 levels, namely K1 (Straw Fertilizer) and K2 (Cow Manure Fertilizer). The second factor is the dose of Azotobacter which consists of 3 levels, namely A1 (10 ml), A2 (20 ml), A3 (30 ml). The results showed that there was an interaction in the observation of wet weight of green mustard plants. The provision of various types of organic fertilizers showed that the K1 treatment (straw fertilizer) gave the best results in the observation of plant height, number of leaves, and wet weight of mustard green plants. Meanwhile, the application of Azotobacter influenced the observation of wet weight of mustard green plants in the A1 (10 ml) treatment, while the observation of the number of leaves of mustard green plants was obtained by the A2 (20 ml) treatment, and the observation of plant height of mustard green plants was obtained by the A3 (30 ml) treatment